Peran Pendidikan Kewarganegaraan Bagi Pelajar Dalam Mewujudkan Warga Negara Yang Baik Dan Cerdas - Annisa Anastasia Salsabila; Dinie Anggraeni Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of writing this article is for readers to understand the important role of civic education in eliminating the crisis in student character. Because, currently there is a crisis in the character of students in the State of Indonesia. With the change in globalization in the millennial era, it is necessary to question the character of the students in Indonesia. This article is written to describe the role of citizenship education for students in Indonesia in realizing good and smart citizens to live a better life. This shows that with Citizenship Education, there is a great opportunity for this nation to have students with character. The method used in this article is the method of collecting data by means of literature study. This literature study was carried out by collecting data related to problems related to the role of civic education in the millennial era by building the character of students in the State of Indonesia. With the role of civic education, students understand that good character is very much needed in advancing this nation.